IDENTIFIKASI ASAM FENOLAT DARI EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia (Ten.) Stennis) DAN UJI AKTIVITAS ANTIOKSIDAN - Ekaviantiwi, Tyas Ayu (Chem Info Journal, 2013)
Binahong (Anredera cordifolia (Ten.) Stennis) is one of the flower planting that come from Basellaceae family and has been know it has biological activities because there is bioactive compound. Phenolic acids are bioactive compound and widely used as antioxidants. In this study, identification and antioxidant activity test in ethanolic extract of binahong leaves were done. Phenolic acids were isolated without hydrolysis (TH fraction), acid hydrolysis (fraction HA), and alkaline hydrolysis (HB fraction). Based on the identification using TLC with co-chromatography, UV-Vis and FTIR spectrophotometer, detected that ethanolic extract of binahong leaves maybe contain p-coumaric acid. The quantitative analysis using TLC scanner known that the levels of p-coumaric acid of TH fraction, HA fraction, HB fraction are 8.11205%; 3.77526%; and 23.57104% respectively. The antioxidant activity (IC50) of ethanolic extract and isolate B are 866.89831 mg/L and 1263.3333 mg/L respectively. This indicates that B isolates haven’t the potency to be developed as an antioxidant compound cracked.